Correlation of physiological and biological traits in mammalian aging and longevity - Chanda, SachinKumar Veersain (Nanyang Technological University, 2023)
This study aimed to understand the correlation of physiological and biological traits in mammalian aging and longevity by investigating the relationships between heartbeat per lifetime, telomere length, genome size, and p53/TP53 copy numbers in mammals. The data on the aforementioned factors were collected and analyzed. Regression techniques, including OLS multiple regression and the random forest model, were used to explore the underlying relationships.